Impact of antibody to hepatitis B core antigen on the clinical course of hepatitis C virus carriers in a hyperendemic area in Japan: A community‐based cohort study. Issue 11 (18th February 2013) - Tsubouchi, Naoko; Uto, Hirofumi; Kumagai, Kotaro; Sasaki, Fumisato; Kanmura, Shuji; Numata, Masatsugu; Moriuchi, Akihiro; Oketani, Makoto; Ido, Akio; Hayashi, Katsuhiro; Kusumoto, Kazunori; Shimoda, Kazuya; et al.
Abstract : Aim: Subjects positive for antibody to hepatitis B core antigen (HBcAb) and negative for hepatitis B surface antigen (HBsAg) are considered to have occult hepatitis B virus (HBV) infection. The aim of this study was to determine the impact of occult HBV infection on aggravation of the clinical course in hepatitis C virus (HCV) carriers. Methods: A prospective cohort study was performed in 400 subjects who were positive for anti‐HCV antibody and negative for HBsAg. Among these subjects, 263 were HCV core antigen positive or HCV RNA positive (HCV carriers). We examined whether the presence of HBcAb affected the clinical course in these HCV carriers from 1996–2005. Results: The HBcAb positive rates were 53.6% and 52.6% in HCV carriers and HCV RNA negative subjects, respectively. There were no differences in the incidence of hepatocellular carcinoma (HCC) and cumulative mortality associated with liver‐related death between HCV carriers who were positive and negative for HBcAb. In multivariate analysis, age (≥65 years) and alanine aminotransferase level (≥31 IU/L) emerged as independent risk factors for HCC development and liver‐related death, but the HBcAb status was not a risk factor. In addition, increased serum hepatic fibrosis markers (measured from 2001–2004) were not associated with HBcAb status. Conclusion: In our cohort study, the presence of HBcAb had no impact on HCC development, liver‐related death and hepatic fibrosis markers in HCV carriers. Thus, our results indicate that occult HBV infection has no impact on the clinical course in HCV carriers.